A simulation study of the low temperature phase diagram of the methane monolayer on graphite: a test of potential energy functions. Issue 30 (21st July 2020) - Zhang, Han; Tan, Shiliang (Johnathan); Prasetyo, Luisa; Do, D. D.; Nicholson, D.
Abstract : The TraPPE-EH model reveals the two patterns of commensurate monolayer and the mechanism of commensurate–incommensurate transition in a certain temperature range. Abstract : We have used molecular simulation with two intermolecular potential models, TraPPE-UA and TraPPE-EH, the latter of which accounts for the tetrahedral shape, to study the effects of shape on methane adsorption on graphite. Both models give good descriptions of the vapour–liquid equilibria in the bulk phase, but adsorption on graphite is better described by the TraPPE-EH model. Molecular configurations in the monolayer, show the variation with temperature of the registry sites for the carbon and hydrogen atoms of the methane molecules. At temperatures below 70 K, the centre of mass (COM) of the molecules is in registry with the centre of the carbon hexagons. For temperatures above 70 K, a commensurate monolayer is initially formed as at low temperatures, then as the loading is increased the first layer remains in registry, but the COM of the methane molecules in the first layer shifts to the top of the graphite carbon atoms with the C–H bond pointing to carbon atoms in the second shell of a C-hexagon. At temperatures above 93 K, the first adsorbate layer goes through these two commensurate states and then undergoes a transition to an incommensurate solid. Finally, for temperatures greater than 110 K methane behaves like a pseudo spherical molecule.